Turning the tide on inequity through systematic equity action-analysis - Katrina M. Plamondon; Jenna Dixon; Ben Brisbois; Rodrigo Curty Pereira; Elijah Bisung; Susan J. Elliott; Ian D. Graham; Sume Ndumbe-Eyoh; Stephanie Nixon; Sana Shahram (BMC, 2023)
Abstract Background Collective agreement about the importance of centering equity in health research, practice, and policy is growing. Yet, responsibility for advancing equity is often situated as belonging to a vague group of 'others', or delegated to the leadership of 'equity-seeking' or 'equity-deserving' groups who are tasked to lead systems transformation while simultaneously navigating the violence and harms of oppression within those same systems. Equity efforts also often overlook the breadth of equity scholarship. Harnessing the potential of current interests in advancing equity requires systematic, evidence-guided, theoretically rigorous ways for people to embrace their own agency and influence over the systems in which they are situated. ln this article, we introduce and describe the Systematic Equity Action-Analysis (SEA) Framework as a tool that translates equity scholarship and evidence into a structured process that leaders, teams, and communities can use to advance equity in their own settings. Methods This framework was derived through a dialogic, critically reflective and scholarly process of integrating methodological insights garnered over years of equity-centred research and practice. Each author, in a variety of ways, brought engaged equity perspectives to the dialogue, bringing practical and lived experience to conversation and writing. Our scholarly dialogue was grounded in critical and relational lenses, and involved synthesis of theory and practice from a broad range of applications and cases. Results The SEA Framework balances practices of agency, humility, critically reflective dialogue, and systems thinking. The framework guides users through four elements of analysis (worldview, coherence, potential, and accountability) to systematically interrogate how and where equity is integrated in a setting or object of action-analysis. Because equity issues are present in virtually all aspects of society, the kinds of 'things' the framework could be applied to is only limited by the imagination of its users. It can inform retrospective or prospective work, by groups external to a policy or practice setting (e.g., using public documents to assess a research funding policy landscape); or internal to a system, policy, or practice setting (e.g., faculty engaging in a critically reflective examination of equity in the undergraduate program they deliver). Conclusions While not a panacea, this unique contribution to the science of health equity equips people to explicitly recognize and interrupt their own entanglements in the intersecting systems of oppression and injustice that produce and uphold inequities.